ANALISIS GEOGRID SEBAGAI TULANGAN PADA DINDING PENAHAN TANAH - Simanjuntak, Johan Oberlyn; Bartholomeus; Saragi, Yetty Riris; Pasaribu, Humisar; Silaban, Arnita (LPPM Universitas HKBP Nommensen, 2021)
The soil reinforcement system or reinforced earth was first introduced by Vidal in 1969. In addition, soil reinforcement has been applied in the construction of dams, embankments, raft foundations and supporting structures for ports and others. With the same concept as reinforced concrete, the reinforcement in the soil is in the form of sheet reinforcement, namely the geogrid relies on its high tensile strength. As concrete resists compression, reinforcement resists tension, so reinforcement in soil is useful for forming composite materials that work together to withstand the loads acting on construction, in this case the construction of retaining walls. In this study, a retaining wall will be analyzed in the form of an arrangement of concrete blocks as high as 6 meters with a foundation width of 2.5 meters and a thickness of 1 meter. On the soil side of the embankment, an analysis will be carried out with and without using a geogrid as reinforcement, where in the analysis of retaining walls with a geogrid several different configurations will be used for each layer thickness of the embankment (SV). The type of embankment soil used is granular soil (cohesiveless) with varying shear angles, f1 = 250, f2 = 300, f3 = 350, and f4 = 400. At the top of the embankment, there are pavement loads and traffic loads. of 15 kN/m. In this study, the retaining wall is planned to be able to withstand the loads acting on it, both from the outside and from the internal. Furthermore, as a comparison of results, to analyze or check the landslide field and stability for embankments using a geogrid and without geogrid, the Finite Element (OptumG2 for academics) method is used. Based on the analysis that has been done, it is found that the denser the geogrid reinforcement used in retaining walls, the higher the safety factor. The shear angle of a soil greatly affects the length of the geogrid. In addition, the smaller the shear angle, the higher the maximum stress value (Tmax) on the geogrid.